Digital Health Management and Physician Behavior in Sustainable Telemedicine Use - Elika Setiawaty; Hartoyo; Rita Nurmalita; Lilik Noor Yuliati (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Telemedicine has become a key component of digital health management in emerging healthcare systems. This study aims to investigate the behavioural drivers of sustainable telemedicine adoption among physicians. An integrative behavioural model was developed by combining the Unified Theory of Acceptance and Use of Technology, Technology Acceptance Model, Innovation Resistance Theory, and Social Cognitive Theory, along with constructs of economic value and social support. A cross-sectional survey of 244 licensed physicians was conducted using purposive sampling, and data were analysed with Partial Least Squares Structural Equation Modelling (PLS-SEM) and Multi-Group Analysis. The results indicate that economic value is the strongest predictor of behavioural intention, while social support is the primary determinant of actual use. Perceived digital risk had no significant impact, underscoring an intention–action gap where readiness does not always lead to sustained behaviour. MGA revealed that physicians with 5–10 years of experience were more sensitive to digital risks, which negatively influenced their intention to adopt. These findings emphasize the importance of economic framing and professional support in closing the intention–action gap and strengthening sustainable telemedicine adoption. The study offers evidence-based insights for managing long-term digital health transformation in developing healthcare contexts.